The association between lifestyle risk score and mental health in Iranian overweight and obese women: a cross-sectional study - Ebrahimi, Sara; Shiraseb, Farideh; Ladaninezhad, Maryam; Navaei, Negin; Izadi, Azimeh; Mirzaei, Khadijeh (Frontiers in Nutrition, 2025)
BackgroundSince evidence on the relationship between a combination of lifestyle factors and mental health in the Iranian population is limited, this study employed a cross-sectional design which is a quick and low-cost method to provide more information on the potential association between lifestyle and mental health. This study addresses this gap by focusing on Iranian overweight and obese women.MethodsThis cross-sectional study analyzed 278 Iranian overweight and obese women. A multistage random sampling method was used to recruit the participants. The lifestyle risk score (LRS) was created based on diet, physical activity (PA), sleep, obesity, and sociodemographic characteristics. Multinomial logistic regression analysis was used to evaluate the association between LRS and the odds of depression, anxiety, and stress. Participants were assigned a score of 0 for each healthy behavior and a score of 1 for each unhealthy behavior. A higher LRS indicates an unhealthier lifestyle. A binary logistic regression analysis was used to examine LRS and the stress and depression anxiety stress scale (DASS).ResultsSignificant positive associations between high LRS and moderate and severe depression were found (p < 0.05). Furthermore, there were significant positive associations between higher LRS and mild and extremely severe stress (p < 0.05).ConclusionThis is the first study that examined associations between LRS and total DASS-21 and demonstrated that participants with lower LRS had lower levels of depression and stress. This study highlights the crucial role of healthy lifestyle choices in psychological wellbeing. These findings inform the design of interventions to address mental health disorders in Iran. Further prospective studies, including a larger sample size of both genders, are needed to expand our understanding of lifestyle scores’ associations with mental health.